Idade e profundidade de transplantio de mudas no crescimento radicular adventício e desenvolvimento do tomateiro para processamento - Castro, Yuri de Oliveira (2017)
Encourage the adventitious roots can bring increments to the culture of tomatoes for industrial processing (TI). The objective of this study was to determine the effect of positions transplanting and ages of adventitious roots in changes in plant development in TI productivity. Three experiments were carried out arranged in factorial scheme (3 x 3 + 2): three positions of transplanting (collect level, at the level of the cotyledon and at the level of the first leaf fully expanded) in three ages of change (30, 60 and 90 days after sowing-DAS) and a free additional position (at the level of the last leaf fully expanded) for the ages of 60 and 90 DAS. The changes of the 30 did not present last leaf fully expanded and did not receive the last position of transplanting. In experiment 1 (one) the contribution of the zones or regions Annals (collect the cotyledon; the cotyledon to the first leaf; the first sheet to the last leaf fully expanded) to the number of roots adventitious issued. The Count took place every two days after transplanting (DAT) and was held until the 20º DAT. The experiment was designed entirely with four replicates and plots sub-plot. In experiment 2 (two) to evaluate the architecture of the root system of seedlings of thee through images of the roots of plants cultivated in rizontrons (phenotyping platform of high performance) and analyzed by software WinRHIZO PRO 2013. The experiment was designed in complete randomized blocks (DBC) with five repetitions. In experiment 3 (three) measured periodically the leaf area and dry mass of aerial part of plants, equations of partition and fotoassimilados allocation. The experiment was designed in DBC with six repetitions. The area between the collect and the cotyledon presented the highest number of adventitious roots in all ages of change, with quadratic responses to 60 and 90 of seedlings and seedlings for 30 DAS. The issue of roots beyond the 20º day may be related to better hormonal and nutritional condition of 30 seedlings of compared with the seedlings of 60 and 90 DAS. The depth of the root system is linked to a greater leaf area, although the contribution of photosynthesis for the adventitious roots become less relevant than other factors such as nutritional status of changes. The leaf area and dry mass of plant organs were influenced by age of change. Seedlings of 30 and 60 DAS the present greater leaf area, dry mass accumulation and distribution of roots when compared with 90 DAS the seedlings. Productivity did not differ between the ages of 30 and 60 DAS and was higher if compared to 90 DAS seedlings.